Modulating mechanisms of pea protein fibrils on the interfacial distribution of diacylglycerol and structural rigidity of emulsion gel - Hu, Bingjie; Lee, Yee Ying; Tan, Chin Ping; Chen, Weihao; Wang, Yong; Qiu, Chaoying (Elsevier B.V., 2025)
Excessive animal fat intake drives interest in developing plant−based gels as sustainable and healthier fat substitutes. However, maintaining a rheology resemblance to animal fat while achieving clean−label and nutritional features remains challenging. This study explores the use of pea protein fibrils (PPF) to enhance the interfacial stability and structural strength of diacylglycerol (DAG) and κ–carrageenan–based emulsion. Primarily, pea protein isolate fibrillated for 20–28 h (PPF) significantly increased the interfacial dilatational modulus. The emulsion showed smaller droplets and high yield stress at oil–water ratios of 6:4–5:5. PPF promoted DAG crystallization and the alignment of crystals at droplet surface which greatly increased the emulsion gel strength, yield stress and structure maintaining ability when subjected to high temperature. The crystallization kinetics results revealed a faster nucleation but slower growth rate mediated by the PPF which changed the crystal distribution. Molecular docking and molecular dynamics simulations confirmed that PPF molecules provided more binding amino acid sites (e.g., Leu, Asn, Arg) with DAG than PPI and adopted a more stable interfacial conformation with closer contact to the center of DAG through hydrogen bonding and hydrophobic interactions. This study reveals that the assembly of PPF with DAG showed a synergistic effect in enhancing interfacial film strength through the redistribution of lipid crystals and provides a novel strategy to fabricate emulsion gels for animal fat replacement.